Pertumbuhan semai saga (Adhenanthera pavonina L.) terhadap pemberian dosis pupuk organik daun lamtoro pada media tumbuh tanah tailing - Fajar, Muh Sultan; Muslimin; Taiyeb, Asgar; Zulkaidhah; Yusran; Megawati, Kartika (Jurnal Bisnis Kehutanan dan Lingkungan, 2024)
The Saga plant (Adhenanthera pavonina L) is a plant that can be used in all parts of the plant, from seeds, wood, bark, stems and leaves. To support the growth of saga seedlings, planting media is needed that contains sufficient nutrients. Providing organic fertilizer can improve the physical, chemical and biological properties of the soil, and can increase the availability of nutrients in the soil. This research was carried out for three months, namely March to June 2023, at the Arboretum Nursery of the Faculty of Forestry, Tadulako University. This research used a Completely Randomized Design (RAL) method with 3 treatments and 7 replications so there were 21 research units. The treatments given were P0= Control, P1=Lamtoro Fertilizer 100 gr/polybag, P2=Lamtoro Fertilizer 150 gr/polybag. Observation parameters were seedling height, stem diameter, and number of leaves. Data were analyzed using analysis of variance (F test). If based on the analysis of variance (F test) there is a significant effect, then the Least Significant Difference (BNT) test is continued at the 5% level. The results of the research showed that treatment with various doses of lamtoro leaf organic fertilizer on ex-mining planting media had a significant effect on the increase in height, diameter and number of leaves on saga seedlings (Adhenanthera pavonina L.). Based on the results of the 5% significant difference test (BNJ), it shows that the average increase in height and diameter of saga seedlings in treatment P2 is significantly different from treatments P1 and P0, but the average leaf growth in treatment P2 is not significantly different. significantly different. significantly different from P1, but significantly different. against P0. The average height increase results are P2=7.4, P1=5.3, P0=2.9. Average increase in diameter P2=2.24mm, P1=0.9mm, P0=0.6mm. The average increase in number of leaves was P2=22.42, P1=20.17 and P0=8.71.